A systematic review and meta-analysis including GRADE qualification of the risk of surgical site infections after prophylactic negative pressure wound therapy compared with conventional dressings in clean and contaminated surgery. Issue 36 (September 2016) - De Vries, Fleur E.E.; Wallert, Elon D.; Solomkin, Joseph S.; Allegranzi, Benedetta; Egger, Matthias; Dellinger, E. Patchen; Boermeester, Marja A.
Abstract : Supplemental Digital Content is available in the text Abstract: Objective: Systematically review and Grading of Recommendations Assessment, Development, and Evaluation (GRADE) studies on prophylactic negative pressure wound therapy (pNPWT) to prevent surgical site infections (SSIs). Introduction: pNPWT has been suggested as a new method to prevent wound complications, specifically SSIs, by its application on closed incisional wounds. Methods: This review was conducted as part of the development of the Global Guidelines for prevention of SSIs commissioned by World Health Organization in Geneva. PubMed, Embase, CENTRAL, CINAHL, and the World Health Organization database between January 1, 1990 and October 7, 2015 were searched. Inclusion criteria were randomized controlled trials and observational studies comparing pNPWT with conventional wound dressings and reporting on the incidence of SSI. Meta-analyses were performed with a random effect model. GRADE Pro software was used to qualify the evidence. Results: Nineteen articles describing 21 studies (6 randomized controlled trials and 15 observational) were included in the review. Summary estimate showed a significant benefit of pNPWT over conventional wound dressings in reducing SSIs in both randomized controlled trials and observational studies, odds ratio of 0.56 (95% confidence interval, 0.32–0.96; P = 0.04) and odds ratio of 0.30 (95% confidence interval, 0.22–0.42; P  < 0.00001), respectively. This translates into lowering the SSI rate from 140 to 83 (49–135) per 1000 patients and from 106 to 34 (25–47) per 1000 patients, respectively. In stratified analyses, these results were consistent in both clean and clean-contaminated procedures and in different types of surgery, however results were no longer significant for orthopaedic/trauma surgery. The level of evidence as qualified with GRADE was however low. Conclusions: Low-quality evidence indicates that prophylactic NPWT significantly reduces the risk of SSIs.